2009
DOI: 10.5027/andgeov36n2-a07
|View full text |Cite
|
Sign up to set email alerts
|

Estratigrafia e inversion tectonica del 'rift' neogeno en el Campo del Arenal, Catamarca, NO Argentina.

Abstract: La cuenca de Santa María-Hualfín en las Sierras Pampeanas del NO de Argentina, comenzó con el fallamiento por extensión de un gran domo orientado NNO-SSE desarrollado sobre basamento cratonizado y peniplanizado. Los bloques fallados adoptaron un diseño basculado hacia fuera del eje del domo preservado hoy en día por la posición de la penillanura. El relleno inicial paleógeno (formaciones Hualfín y Saladillo) aparece asociado a una serie de depocentros asimétricos controlados por fallas normales. Con el ingreso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 4 publications
(12 reference statements)
1
33
0
2
Order By: Relevance
“…6b). In this sector, no Cretaceous syn-rift or post-rift deposits are present (Strecker et al 1989;Mortimer et al 2007;Bossi & Muruaga 2009). Few and small outcrops of the Salta Group deposits are found in the foothills of the eastern slope of the Sierra de Aconquija (Fig.…”
Section: Cross Sectionsmentioning
confidence: 99%
“…6b). In this sector, no Cretaceous syn-rift or post-rift deposits are present (Strecker et al 1989;Mortimer et al 2007;Bossi & Muruaga 2009). Few and small outcrops of the Salta Group deposits are found in the foothills of the eastern slope of the Sierra de Aconquija (Fig.…”
Section: Cross Sectionsmentioning
confidence: 99%
“…1) originated with extension and active faulting from the Paleogene until 4.8 Ma when regional compression began (Bossi and Muruaga 2009). Ages from apatite fission tracks (Sobel and Strecker 2003) suggest a 6 Ma uplift of the Aconquija, Quilmes and Cumbres Calchaquíes Ranges, which arose as deformation migrated to the south (Mortimer et al 2007).…”
Section: A N U S C R I P Tmentioning
confidence: 96%
“…The The new 40 Ar-39 Ar age for the LAF of 9.01±0.12 Ma, is younger than those previously proposed. Bossi and Muruaga (2009) suggested that the LAF was older than 12 Ma because it predated Farallón Negro volcanism. Halter et al (2004) however, dated the Farallón Negro volcanism between 9.4 and 6.3 Ma.…”
Section: 2-age Of the Unit And Chronostratigrafic Correlationmentioning
confidence: 97%
See 1 more Smart Citation
“…CONCLUSÕES ...................................................................................................................... REFERÊNCIAS BIBLIOGRÁFICAS ......................................................................................... Centrais, com contornos das linhas sísmicas e suas profundidades em relação à zona Wadati-Benioff (Bissig, et al, 2002). .................................................................................. Figura 14: Mapa Geológico Regional da zona do Complexo Vulcânico Farallón Negro, com a Serra del Aconquija e localização dos depósitos estudados (Bossi & Muruaga, 2009) .. ........................................................................................................................................... Figura 15: Mapa com lineamentos regionais e os principais depósitos de tipo pórfiro da região. Marcação da Zona de Transferência de Tucumán e dos depósitos estudados na tese (Roy et al, 2006) Rica, BHP 1998 e Landtwing et al, 2002.…”
Section: Introductionunclassified